The Representation of the Chinese Modal Particles a(啊), ba(吧) and ne(呢) Within High-Context Communication—Based on the Corpus Findings of Chinese Learners Cognition - Song, Guangrong (Trinity College (Dublin, Ireland). School of Education, 2021)
As the Chinese Modal Particles make up the hardest learning content for Chinese learners, this dissertation focuses on a(啊), ba(吧), and ne(呢) to explore Chinese learner acquisition and cognition, and how the Chinese Modal Particles embody high-context communication. The study is based on the High-context Theory and the Usage-Based Approaches Theory and uses Contrastive Interlanguage Analysis as the primary study method to compare the Chinese learner corpus and the L1 Chinese corpus. The two corpora are Guangwai-Lancaster Chinese Learner Corpus and “ZhouDinner” in CHILDES-TALK BANK. The study then collects quantitative and qualitative data to analyse the usage differences between the two corpora and the acquisition features in the Chinese learner corpus, and the relationship between Chinese Modal Particles and high-context communication in a full discourse.
Keywords: Language Education; Education